Meningkatkan Minat Baca Masyarakat melalui Pembentukan Taman Baca Masyarakat di Dusun Wetan, Desa Utama, Kabupaten Ciamis - Tia, Ade; Muflihah, Ai; Widianingsih, Ai; Rahayu, Ajeng Widya; Alipudin, Alipudin; Heryani, Nia; Fatimah, Mia Nurul; Fahleviyani, Riza Dwi; Yuliani, Ai Lia (Khidmat, 2021)
The low interest in learning and reading in the community is increasingly felt and seen, the entry of the 4.0 era where everything is fixated on technology which makes all people, especially children of productive age, focus on their gadgets and are so receptive to spreading information that is not filtered first, driven by the pandemic. Covid-19, which requires children to study at home, makes them even more lazy to read books and think, only relying on Google as an alternative way of doing assignments. In realizing a community that likes to learn through a love of reading, the establishment of a Community Reading Park (TBM) Community reading park is a means to serve the interests of the people who live around it consisting of various layers of society without distinguishing between social, economic, cultural, religious, customs, educational backgrounds. , age and so on and this can be one solution, if viewed from the geographical location for the Main village itself, access to visit the regional public library takes 35 minutes and it is impossible for elementary school children to travel unless accompanied by their parents, from Here the role of TBM is very important and strategic because TBM is also established by, for, and in the midst of the community and the learning process is not only focused on reading but on writing and arithmetic which needs to be improved. The purpose of the formation of this TBM is to educate the surrounding community. It was founded and managed by community members who have motivation and ideals and started from the existence of Real Work Lectures in their own villages (KKN) assisted by people who care about children, have low reading interest and have high hopes for TBM. will remain active even though the Community Service Program has ended, the enthusiasm of the community, especially the children, is increasing every day in reading and knowing various kinds of stories as well as writing and counting. The conclusion in this article is that through the formation of TBM can improve student learning outcomes in learning to write, read and count.